Slang Words in Transaction of Selling-Buying Drugs in Padang City Area - Amelia Yuli Astuti; Bram Denafri (Fakultas Sastra Universitas Ekasakti, 2020)
This research is able to develop linguistic aspects that are used by a group of drug dealers and users to be directly identified by people who are likely close to them. So that the public can be aware of the existence of drug sales transactions and submit it to the authorities to follow up. This research seeks to understand and explain the phenomena of slang used by drug dealers in buying and selling transactions Padang City. This research produces descriptive data in the form of sentences, words, or slang language phrases Padang City. This research method is Simak Libat Cakap (SLC) where researchers are directly involved in obtaining data. Sources of data in this research were obtained from oral sources. The oral data source was obtained from an interview with one dealer who was willing to be interviewed who did the distribution and had connections with other dealers.